Targeting the Carbonic Anhydrase Enzyme with Synthesized Benzenesulfonamide Derivatives: Inhibiting Tumor Growth - Kifah Abbas, Zainab; Naser, Noor H.; Atiya, Rana Neama (Journal of Contemporary Medical Sciences, 2023)
Objectives: To assess the anticancer effects of recently developed compounds, Sa, Sb, Sc, and Sd. These compounds were designed to specifically target the carbonic anhydrase enzyme in solid tumors. Methods: The chemical synthesis involved the use of sulfanilamide, chloroacetyl chloride, GABA, thionyl chloride, methanol, hydrazine hydrate, potassium hydroxide, carbon disulfide, and benzyl chloride derivatives. Docking studies were conducted using the MOE software program version 2015.10, and cytotoxic activity was predicted using the MTT assay. Results: The newly synthesized compounds exhibited notable antineoplastic activity in both in silico and cell line investigations. Although they showed a significant difference in potency compared to cisplatin against cancer cells, they also demonstrated significant differences in toxicity towards normal cells. When compared to acetazolamide, compounds Sb displayed an IC50 = 28.41 μM, which was significantly different, and compound Sd showed a non-significant difference with an IC50 = 61.20 μM against MCF7 cells. Additionally, Sb and Sd demonstrated significant difference in toxicity, with IC50 = 279.02 μM and 194.00 μM, respectively, against MCF10a cells. These findings indicate a significant difference compared to acetazolamide for the Sb compound and suggest that the synthesized compounds hold potential for further development as antineoplastic agents. Furthermore, the results from the cell line study align with the in silico study, where both compounds Sb and Sd exhibited higher S scores compared to acetazolamide, implying a stronger binding affinity with the receptor's catalytic site. The presence of a substituted 1,2,4-triazole ring in these compounds contributed to enhanced flexibility and improved interaction with the receptor. Conclusion: A new synthesized compounds exhibited cytotoxicity and demonstrated inhibitory potencies against carbonic anhydrase.